Carbonatação acelerada em concretos compostos com cinza de casca de arroz de diferentes teores de carbono grafítico - Nunes, Douglas Garcez (2014)
Carbonation is a natural phenomenon observed in carbon structures, and it is a result of the combined presence of CO2 in the environment and moisture. Carbonation may lower the pH of the concrete to such an extent that the passivation layer of the steel is depleted and the onset of frame corrosion is observed, which is one of the major pathologies in reinforced concrete structures. This study aimed to assess accelerated carbonation in concrete samples prepared with rice husk ash (RHA) with different concentrations of graphitic carbon and different curing periods. Concrete samples were prepared with 5%, 10%, 20% and 30% of RHA as a substitution for high early strength Portland cement (Brazilian grade CPV-ARI), different water/binder ratios (0.35; 0.50; 0.65) and wet cured for 3 and 7 days. In addition, two mixes with 5% and 10% silica fume as substitutions for Portland cement were used for comparison. Accelerated carbonation was performed in 10x10cm test specimens (TS) that were preconditioned as determined by standard RILEM TC 116-PCD. These TSs were stored in a controlled temperature chamber (RH 65 ± 2%, temperature 23 ± 2°C, 3% CO2 b/v), where they were exposed to CO2 for 4, 8, 12 and 16 weeks. The mercury intrusion porosimetry test was performed in 4x8cm TSs, which were tested after 91 days. Overall results show improved accelerated carbonation performance in the samples prepared with rice husk ash with lower concentrations of graphitic carbon, even though figures were similar. Higher concentrations of RHA in the concrete samples resulted in increased carbonation coefficients for all mixes investigated. For samples of the same strength values, a reduction in carbonation coefficients was observed when their compressive strength increased from 40 MPa to 50 MPa, This was seen in all mixes investigated for the curing period used, which shows that the use of longer curing periods improves the service life of structures.